Pengaruh Kualitas Pelayanan, Motivasi Berkoperasi dan Lokasi Usaha terhadap Partisipasi Anggota Koperasi Unit Desa (Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the effect of service quality, cooperative motivation, business location on the participation of members of KUD Jatinom, Klaten Regency, (2) either partially or simultaneously. The population of this research is the members of KUD Jatinom, Klaten Regency as many as 6150 members, and the sample is taken as many as 100 members. Data were collected by questionnaire and analyzed descriptively and multiple linear regression analysis. The results showed that there was a simultaneous effect of service quality, cooperative motivation, business location on the participation of KUD Jatinom members, Klaten Regency of 76.1%, partially service quality had a positive and significant effect on member participation of 5.24%, positive and significant cooperative motivation. on member participation by 24.5% and business location has a negative effect on member participation.